Islamic Economics during the Glorious Period of the Abbasid Dynasty: Social and Cultural Transformation - Merly Cahya Putri (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
This study examines the transformation of the Islamic economy during the golden age of the Abbasid Dynasty, characterized by innovations in financial systems, the implementation of fiscal policies based on wealth redistribution, and shifts in social and cultural structures. The background of this research is rooted in the strategic role of the Abbasid Dynasty in creating an advanced Islamic civilization through the integration of economic progress, social growth, and cultural development. The aim of the study is to analyze in depth the dynamics of economic change, its impact on social structures, and its contribution to the development of science and culture during this period. The method employed is a Systematic Literature Review (SLR), which involves the search, selection, and synthesis of literature from various credible academic sources. The findings indicate that innovative policies, such as the implementation of primitive banking systems, zakat and waqf mechanisms, and infrastructure development, support inclusive economic growth and equitable wealth distribution. The implications of this study suggest that the principles of the Islamic economy implemented during the Abbasid era can serve as a reference in designing modern economic policies that are just, sustainable, and responsive to socio-cultural dynamics.